In vitro Conservation and Exploiting Polyembryonate Potential of Synthetic Seeds of Malaxis acuminata D. Don (Plant Tissue Culture and Biotechnology, 2023)
Synthetic seeds were prepared in Malaxis acuminata by encapsulating shoot tip derived protocorm-like bodies (PLBs; 0.2-0.5 cm) in a hydrated gel capsule composed of calcium alginate matrix (sodium alginate; 3.5% and calcium chloride; 75 mM) in liquid Murashige and Skoog, 1962 (MS) medium. Synthetic seeds varied in physical features with the concentration of gelling agent and calcium chloride. In in vitro germination, the optimum response was achieved in MS medium fortified with BAP (1mgl-1); where synthetic seeds germinated with 100% frequency. Physically firm, globular, non-leaky, and self-breaking beads germinated efficiently which could be stored for up to 90 days at 4℃. At room temperature, synthetic seeds germinated with 50% frequency after 15 days and the germination frequency steadily reduced to 0% after 45 days of storage. Under in vivo conditions, synthetic seeds showed 80% bead-to-plant conversion in MS medium supplemented with antibacterial, antifungal agents and BAP (1mg/I). Plant Tissue Cult. & Biotech. 33(1): 9-15, 2023 (June)